A generic concept to overcome bandgap limitations for designing highly efficient multi-junction photovoltaic cells - Guo, Fei; Li, Ning; Fecher, Frank W.; Gasparini, Nicola; Ramírez Quiroz, César Omar; Bronnbauer, Carina; Hou, Yi; Radmilovic, Vuk V.; Radmilovic, Velimir R.; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Nature Communications, 2015)
The multi-junction concept is the most relevant approach to overcome the Shockley-Queisser limit for single-junction photovoltaic cells. The record efficiencies of several types of solar technologies are held by series-connected tandem configurations. However, the stringent current-matching criterion presents primarily a material challenge and permanently requires developing and processing novel semiconductors with desired bandgaps and thicknesses. Here we report a generic concept to alleviate this limitation. By integrating series- and parallel-interconnections into a triple-junction configuration, we find significantly relaxed material selection and current-matching constraints. To illustrate the versatile applicability of the proposed triple-junction concept, organic and organic-inorganic hybrid triple-junction solar cells are constructed by printing methods. High fill factors up to 68% without resistive losses are achieved for both organic and hybrid triple-junction devices. Series/parallel triple-junction cells with organic, as well as perovskite-based subcells may become a key technology to further advance the efficiency roadmap of the existing photovoltaic technologies.
Keywords: GEOBASE Subject Index: fuel cell; photovoltaic system; solar power EMTREE medical terms: Article; electric current; electric potential; electrical equipment; multi junction photovoltaic cell

Detailed optical modelling and light-management of thin-film organic solar cells with consideration of small-area effects - Lipovšek, Benjamin; Čampa, Andrej; Guo, Fei; Brabec, Christoph; Forberich, Karen; Krč, Janez; Topič, Marko (Optics Express, 2017)
We present detailed numerical and experimental investigation of thin-film organic solar cells with a micro-textured light management foil applied on top of the front glass substrate. We first demonstrate that measurements of small-area laboratory solar cells are susceptible to a significant amount of optical losses that could lead to false interpretation of the measurement results. Using the combined optical model CROWM calibrated with realistic optical properties of organic films and other layers, we identify the origins of these losses and quantify the extent of their influence. Further on, we identify the most important light management mechanisms of the micro-textured foil, among which the prevention of light escaping at the front side of the cell is revealed as the dominant one. Detailed three-dimensional simulations show that the light-management foil applied on top of a large-area organic solar cell can reduce the total reflection losses by nearly 60% and improve the short-circuit current density by almost 20%. Finally, by assuming realistic open-circuit voltage and especially the realistic fill factor that deteriorates as the absorber layer thickness is increased, we determine the optimal absorber layer thickness that would result in the highest power conversion efficiency of the investigated organic solar cells.
Keywords: Engineering controlled terms: Open circuit voltage; Optical films; Optical properties; Organic solar cells; Substrates; Thin film solar cells; Thin films Experimental investigations; Glass substrates; Light management; Optical modeling; Optical modelling; Power conversion efficiencies; Three dimensional simulations; Total reflection Engineering main heading: Solar cells

Efficiency Limits and Color of Semitransparent Organic Solar Cells for Application in Building-Integrated Photovoltaics - Forberich, Karen; Guo, Fei; Bronnbauer, Carina; Brabec, Christoph (Energy Technology, 2015)
We have modified the well-known Scharber model for the efficiency limits of organic solar cells for the case of semitransparent devices, which are considered as one of the most promising applications for this photovoltaic (PV) technology. We introduce a modified external quantum efficiency (EQE) relation and derive the transparency from the convolution of the calculated transmittance spectrum with the human eye sensitivity. We find that the design guidelines for the optimum band gap of the absorber material have to be carefully adapted for the desired transparency, especially for transparency values exceeding 40%. In addition, we examine the relationship between efficiency, transmitted color, and band gap and conclude that high efficiencies can be achieved for a wide range of colors. Our model shows good agreement with experimental values from the literature and can be easily adapted to different applications (e.g., greenhouses) by using the appropriate spectrum. © 2015 WILEY-VCH Verlag GmbH & Co.
Keywords: Building-integrated photovoltaics; Organic solar cells; Photovoltaics; Scharber model; Semitransparency

Exploring the Limiting Open-Circuit Voltage and the Voltage Loss Mechanism in Planar CH3NH3PbBr3 Perovskite Solar Cells - Chen, Shi; Hou, Yi; Chen, Haiwei; Richter, Moses; Guo, Fei; Kahmann, Simon; Tang, Xiaofeng; Stubhan, Tobias; Zhang, Hong; Li, Ning; Gasparini, Nicola; Ramírez Quiroz, César Omar; et al. (Advanced Energy Materials, 2016)
Perovskite solar cells based on CHNHPbBr with a band gap of 2.3 eV are attracting intense research interests due to their high open-circuit voltage (V) potential, which is specifically relevant for the use in tandem configuration or spectral splitting. Many efforts have been performed to optimize the V of CHNHPbBr solar cells; however, the limiting V (namely, radiative V:V) and the corresponding ΔV (the difference between V and V) mechanism are still unknown. Here, the average V of 1.50 V with the maximum value of 1.53 V at room temperature is achieved for a CHNHPbBr solar cell. External quantum efficiency measurements with electroluminescence spectroscopy determine the V of CHNHPbBr cells with 1.95 V and a ΔV of 0.45 V at 295 K. When the temperature declines from 295 to 200 K, the obtained V remains comparably stable in the vicinity of 1.5 V while the corresponding ΔV values show a more significant increase. Our findings suggest that the V of CHNHPbBr cells is primarily limited by the interface losses induced by the charge extraction layer rather than by bulk dominated recombination losses. These findings are important for developing strategies how to further enhance the V of CHNHPbBr-based solar cells.
Keywords: CH3NH3PbBr3 solar cells; interface materials based losses; nonradiative recombination losses; open-circuit voltage

Extending the environmental lifetime of unpackaged perovskite solar cells through interfacial design - Chen, Haiwei; Hou, Yi; Halbig, Christian Eberhard; Chen, Shi; Zhang, Hong; Li, Ning; Guo, Fei; Tang, Xiaofeng; Gasparini, Nicola; Levchuk, Ievgen; Kahmann, Simon; Ramírez Quiroz, César Omar; et al. (Journal of Materials Chemistry A, 2016)
Solution-processed oxo-functionalized graphene (oxo-G) is employed to substitute hydrophilic PEDOT:PSS as an anode interfacial layer for perovskite solar cells. The resulting devices exhibit a reasonably high power conversion efficiency (PCE) of 15.2% in the planar inverted architecture with oxo-G as a hole transporting material (HTM), and most importantly, deploy the full open-circuit voltage (V) of up to 1.1 V. Moreover, oxo-G effectively slows down the ingress of water vapor into the device stack resulting in significantly enhanced environmental stability of unpackaged cells under illumination with 80% of the initial PCE being reached after 500 h. Without encapsulation, ∼60% of the initial PCE is retained after ∼1000 h of light soaking under 0.5 sun and ambient conditions maintaining the temperature beneath 30 °C. Moreover, the unsealed perovskite device retains 92% of its initial PCE after about 1900 h under ambient conditions and in the dark. Our results underpin that controlling water diffusion into perovskite cells through advanced interface engineering is a crucial step towards prolonged environmental stability.
Keywords: Engineering controlled terms: Cell engineering; Conducting polymers; Open circuit voltage; Perovskite; Slow light; Solar cells Environmental stability; Functionalized graphene; High power conversion; Hole-transporting materials; Interface engineering; Interfacial design; Inverted architectures; Solution-processed Engineering main heading: Perovskite solar cells

Fully printed organic tandem solar cells using solution-processed silver nanowires and opaque silver as charge collecting electrodes - Guo, Fei; Li, Ning; Radmilovic, Vuk V.; Radmilovic, Velimir R.; Turbiez, Mathieu; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Energy and Environmental Science, 2015)
We report in this work efficient, fully printed tandem organic solar cells (OSCs) using solution-processed silver as the reflective bottom electrode and silver nanowires as the transparent top electrode. Employing two different band-gap photoactive materials with complementary absorption, the tandem OSCs are fully printed under ambient conditions without the use of indium tin oxide and vacuum-based deposition. The fully printed tandem devices achieve power conversion efficiencies of 5.81% (on glass) and 4.85% (on flexible substrate) without open circuit voltage (Voc) losses. These results represent an important progress towards the realization of low-cost tandem OSCs by demonstrating the possibility of printing efficient organic tandem devices under ambient conditions onto production relevant carrier substrates.

Fully Solution-Processed Small Molecule Semitransparent Solar Cells: Optimization of Transparent Cathode Architecture and Four Absorbing Layers - Min, Jie; Bronnbauer, Carina; Zhang, Zhi-Guo; Cui, Chaohua; Luponosov, Yuriy N.; Ata, Ibrahim; Schweizer, Peter; Przybilla, Thomas; Guo, Fei; Ameri, Tayebeh; Forberich, Karen; Spiecker, Erdmann; et al. (Advanced Functional Materials, 2016)
Semitransparent solar cells (SSCs) can open photovoltaic applications in many commercial areas, such as power-generating windows and building integrated photovoltaics. This study successfully demonstrates solution-processed small molecule SSCs with a conventional configuration for the presently tested material systems, namely BDTT-S-TR:PCBM, N(Ph-2T-DCN-Et):PCBM, SMPV1:PCBM, and UU07:PCBM. The top transparent cathode coated through solution processes employs a highly transparent silver nanowire as electrode together with a combination interface bilayer of zinc oxide nanoparticles (ZnO) and a perylene diimide derivative (PDINO). This ZnO/PDINO bilayer not only serves as an effective cathode buffer layer but also acts as a protective film on top of the active layer. With this integrated contribution, this study achieves a power conversion efficiency (PCE) of 3.62% for fully solution-processed SSCs based on BDTT-S-TR system. Furthermore, the other three systems with various colors exhibited the PCEs close to 3% as expected from simulations, demonstrate the practicality and versatility of this printed semitransparent device architecture for small molecule systems. This work amplifies the potential of small molecule solar cells for window integration.
Keywords: building integrated photovoltaics; interface bilayer; power conversion efficiency; semitransparent solar cells; small molecule

Fully Solution-Processing Route toward Highly Transparent Polymer Solar Cells - Guo, Fei; Kubis, Peter; Stubhan, Tobias; Li, Ning; Baran, Derya; Przybilla, Thomas; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (ACS Applied Materials and Interfaces, 2014)
We report highly transparent polymer solar cells using metallic silver nanowires (AgNWs) as both the electron- and hole-collecting electrodes. The entire stack of the devices is processed from solution using a doctor blading technique. A thin layer of zinc oxide nanoparticles is introduced between photoactive layer and top AgNW electrode which plays decisive roles in device functionality: it serves as a mechanical foundation which allows the solution-deposition of top AgNWs, and more importantly it facilitates charge carriers extraction due to the better energy level alignment and the formation of ohmic contacts between the active layer/ZnO and ZnO/AgNWs. The resulting semitransparent polymer:fullerene solar cells showed a power conversion efficiency of 2.9%, which is 72% of the efficiency of an opaque reference device. Moreover, an average transmittance of 41% in the wavelength range of 400-800 nm is achieved, which is of particular interest for applications in transparent architectures.
Keywords: semitransparent polymer solar cells; fully solution processing; OPV; ITO-free

High fill factor polymer solar cells comprising a transparent, low temperature solution processed doped metal oxide/metal nanowire composite electrode - Stubhan, Tobias; Krantz, Johannes; Li, Ning; Guo, Fei; Litzov, Ivan; Steidl, Matthias; Richter, Moses; Matt, Gebhard; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
In this paper we report on the replacement for the commonly used ITO electrode material by a low temperature solution processed silver nanowire/(doped) metal oxide composite. Devices employing silver nanowires (AgNWs)/buffer layer electrodes with a photoactive layer of poly(3- hexylthiophene) (P3HT) and [6,6]-phenyl-C butyric acid methyl ester (PCBM) are showing a comparable performance to the ITO reference cell with fill factors (FF) of over 62% and a power conversion efficiency of ∼2.7%. Zinc oxide (ZnO) and highly conductive Al doped ZnO (AZO) are used as buffer layer. AgNW devices without a buffer layer have a high open circuit voltage (V ) but the FF and the short circuit current density (j ) are substantially lower. Overall it is demonstrated that AgNWs and the low temperature solution process of the buffer layer are an attractive device concept towards an indium free organic solar cell. © 2012 Elsevier B.V. All rights reserved.
Keywords: Aluminum-doped zinc oxide; Metal nanowires; Organic solar cells; Solution processed; Transparent electrode; Zinc oxide

High-performance semitransparent perovskite solar cells with solution-processed silver nanowires as top electrodes - Guo, Fei; Azimi, Seyed Hamed; Hou, Yi; Przybilla, Thomas; Hu, Mengyao; Bronnbauer, Carina; Langner, Stefan; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Nanoscale, 2015)
In this work, we report efficient semitransparent perovskite solar cells using solution-processed silver nanowires (AgNWs) as top electrodes. A thin layer of zinc oxide nanoparticles is introduced beneath the AgNWs, which fulfills two essential functionalities: it ensures ohmic contact between the PC60BM and the AgNWs and it serves as a physical foundation that enables the solution-deposition of AgNWs without causing damage to the underlying perovskite. The as-fabricated semitransparent perovskite cells show a high fill factor of 66.8%, V-oc = 0.964 V, J(sc) = 13.18 mA cm(-2), yielding an overall efficiency of 8.49% which corresponds to 80% of the reference devices with reflective opaque electrode

Interface Engineering of Perovskite Hybrid Solar Cells with Solution-Processed Perylene–Diimide Heterojunctions toward High Performance - Min, Jie; Zhang, Zhi-Guo; Hou, Yi; Ramírez Quiroz, César Omar; Przybilla, Thomas; Bronnbauer, Carina; Guo, Fei; Forberich, Karen; Azimi, Seyed Hamed; Ameri, Tayebeh; Spiecker, Erdmann; Li, Yongfang; et al. (Chemistry of Materials, 2015)
Perovskite hybrid solar cells (pero-HSCs) were demonstrated to be among the most promising candidates within the emerging photovoltaic materials with respect to their power conversion efficiency (PCE) and inexpensive fabrication. Further PCE enhancement mainly relies on minimizing the interface losses via interface engineering and the quality of the perovskite film. Here, we demonstrate that the PCEs of pero-HSCs are significantly increased to 14.0% by incorporation of a solution-processed perylene–diimide (PDINO) as cathode interface layer between the [6,6]-phenyl-C61 butyric acid methyl ester (PCBM) layer and the top Ag electrode. Notably, for PDINO-based devices, prominent PCEs over 13% are achieved within a wide range of the PDINO thicknesses (5–24 nm). Without the PDINO layer, the best PCE of the reference PCBM/Ag device was only 10.0%. The PCBM/PDINO/Ag devices also outperformed the PCBM/ZnO/Ag devices (11.3%) with the well-established zinc oxide (ZnO) cathode interface layer. This enhanced performance is due to the formation of a highly qualitative contact between PDINO and the top Ag electrode, leading to reduced series resistance (Rs) and enhanced shunt resistance (Rsh) values. This study opens the door for the integration of a new class of easily-accessible, solution-processed high-performance interfacial materials for pero-HSCs.

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Nanowire Interconnects for Printed Large-Area Semitransparent Organic Photovoltaic Modules - Guo, Fei; Kubis, Peter; Przybilla, Thomas; Spiecker, Erdmann; Hollmann, Andre; Langner, Stefan; Forberich, Karen; Brabec, Christoph (Advanced Energy Materials, 2015)
Semitransparent organic photovoltaic (OPV) cells promise applications in various transparent architectures where their opaque counterparts cannot contribute. Realizing practical applications of this technology requires the manufacturing of large-area modules without significant performance loss compared to the lab-scale devices. In this work, efficient semitransparent OPV modules based on ultrafast laser patterning on both glass and flexible substrates are reported. Solution-processed metallic silver nanowires (AgNWs) are used as transparent top electrodes. The efficient low-ohmic contact of the interconnects between the top AgNWs and the bottom electrode in combination with high-precision laser beam positioning system allow to fabricate semitransparent modules with high electrical fill factor of approximate to 63% and a remarkable geometric fill factor exceeding 95%, respectively. These results represent an important progress toward upscaling of high-performance OPV modules with reduced production costs.

Patterning of OPV modules by ultra-fast laser - Kubis, Peter; Lucera, Luca; Guo, Fei; Spyropoulos, Georgios; Voigt, Monika; Brabec, Christoph (Laser Processing and Fabrication for Solar, Displays, and Optoelectronic Devices III, 2014)
A novel production process combining slot-die coating, transparent exible IMI (ITO-Metal-ITO) electrodes and ultra-fast laser ablation can be used for the realization of P3HT:PCBM based thin film exible OPV modules. The fast and precise laser ablation allows an overall efficiency over 3 % and a device geometric fill factor (GFF) over 95 %. Three functional layers can be ablated using the same wavelength only with varying the laser uence and overlap. Different OPV device architectures with multilayers utilizing various materials are challenging for ablation but can be structured by using a systematical approach.
Keywords: Exible OPV module; Laser ablation; Semitransparent OPV module; Slot-die coating; Ultra-fast laser

Printable Dielectric Mirrors with Easily Adjustable and Well-Defined Reflection Maxima for Semitransparent Organic Solar Cells - Bronnbauer, Carina; Hornich, Julian; Gasparini, Nicola; Guo, Fei; Hartmeier, Benjamin; Luechinger, Norman A.; Pflaum, Christoph; Brabec, Christoph; Forberich, Karen (Advanced Optical Materials, 2015)
Building integrated semitransparent thin-film solar cells is a strategy for future eco-friendly power generation. Organic photovoltaics in combination with dielectric mirrors (DMs) are a potential candidate as they promise high efficiencies in parallel to the possibility to adjust the color and thus the transparency of the whole device. A fully solution processed and printable DM with an easily adjustable reflection maximum is presented that can be facilely attached to solar cells. The DM is optimized via optical simulations to the particular needs of the device with regard to photocurrent enhancement. The excellent agreement between experimental and theoretical results confirms the high optical quality of the printed layers with respect to homogeneity and surface roughness. The used inks are organic-inorganic nanocomposites with a large refractive index contrast of ≈0.7. The short-circuit current is enhanced by up to ≈24% for a semitransparent polymer solar cell.
Keywords: Dielectric mirrors; Organic photovoltaics; Printing; Refractive indices; Semitransparent

Printed Smart Photovoltaic Window Integrated with an Energy-Saving Thermochromic Layer - Guo, Fei; Chen, Shi; Chen, Zhang; Luo, Hongjie; Gao, Yanfeng; Przybilla, Thomas; Spiecker, Erdmann; Osvet, Andres; Forberich, Karen; Brabec, Christoph (Advanced Optical Materials, 2015)
A smart photovoltaic window is designed and constructed by solution-processing a layer of thermochromic VO2 nanoparticles on top of a semitransparent organic solar cell. The prepared smart window not only produces electricity using the visible part of the solar spectrum but also saves energy via intelligently modulating the amount of NIR radiation passing through the device in response to ambient temperature.

Semitransparent organic photovoltaic modules with Ag nanowire top electrodes - Guo, Fei; Kubis, Peter; Przybilla, Thomas; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (International Society for Optical Engineering; 1999, 2014)
Semitransparent organic photovoltaic (OPV) cells are promising for applications in transparent architectures where their opaque counterparts are not suitable. Manufacturing of large-area modules without performance losses compared to their lab-scale devices is a key step towards practical applications of this PV technology. In this paper, we report the use of solution-processed silver nanowires as top electrodes and fabricate semitransparent OPV modules based on ultra-fast laser scribing. Through a rational choice of device architecture in combination with high-precision laser patterning, we demonstrate efficient semitransparent modules with comparable performance as compared to the reference devices.
Keywords: semitransparent organic solar cells; organic photovoltaic modules; silver nanowires; laser patterning

Semitransparent polymer solar cells - Guo, Fei; Ameri, Tayebeh; Forberich, Karen; Brabec, Christoph (Polymer International, 2013)
This perspective discusses the choice of semiconducting photoactive polymers toward high efficiencies of semitransparent polymer solar cells and stresses several promising alternative transparent electrodes to ITO and their processing methods. Bulk heterojunction based polymer:fullerene solar cells have attracted intensive research interest both in academic and industrial communities in the last two decades, mainly related to their potential low-cost production process. A power conversion efficiency of over 10% has been reported recently, making the commercialization of this clean and cheap solar energy convertor a realistic prospect for the near future. The intrinsic features of semitransparency and color tunability of the thin polymeric photoactive films are the greatest asset for polymer solar cells. Recently, aesthetic semitransparent polymer solar cells (ST-PSCs) that can be integrated into transparent windows, roofs, glass and other semitransparent architectural elements have received much attention. In this perspective paper, we present the progress in achieving high performance ST-PSCs, discuss the requirements for transparent electrodes, focusing on alternatives to tin-doped indium oxide, and address the challenges ahead to make ST-PSC viable for real applications. © 2013 Society of Chemical Industry.
Keywords: Bulk heterojunction; OPV; Polymer solar cells; Semitransparent; Silver nanowire

Solution-Processed Parallel Tandem Polymer Solar Cells Using Silver Nanowires as Intermediate Electrode - Guo, Fei; Kubis, Peter; Li, Ning; Przybilla, Thomas; Matt, Gebhard; Stubhan, Tobias; Ameri, Tayebeh; Butz, Benjamin; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Acs Nano, 2014)
Tandem architecture is the most relevant concept to overcome the efficiency limit of single-junction photovoltaic solar cells. Series-connected tandem polymer solar cells (PSCs) have advanced rapidly during the past decade. In contrast, the development of parallel-connected tandem cells is lagging far behind due to the big challenge in establishing an efficient interlayer with high transparency and high in-plane conductivity. Here, we report all-solution fabrication of parallel tandem PSCs using silver nanowires as intermediate charge collecting electrode. Through a rational interface design, a robust interlayer is established, enabling the efficient extraction and transport of electrons from subcells. The resulting parallel tandem cells exhibit high fill factors of similar to 60% and enhanced current densities which are identical to the sum of the current densities of the subcells. These results suggest that solution-processed parallel tandem configuration provides an alternative avenue toward high performance photovoltaic devices.
Keywords: parallel-tandem; polymer solar cells; solution-processed; silver nanowires

Sub-bandgap photon harvesting for organic solar cells via integrating up-conversion nanophosphors - Chen, Wei; Hou, Yi; Osvet, Andres; Guo, Fei; Kubis, Peter; Batentschuk, Miroslaw; Winter, Benjamin; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Organic Electronics, 2015)
Lanthanide-doped up-conversion nanophosphors were employed as up-conversion converters (UC-converters) combined with organic solar cells (OSCs). The optical properties of the external up-conversion layers were investigated, and the optimized layers were laminated with OSCs. Strong photocurrents were observed when OSCs with an UC converter were illuminated by a NIR laser. An improvement of photocurrent and efficiency were also observed under AM 1.5 G sun irradiation. Our investigations show a proof-of-concept that organic solar cells could utilize sub-bandgap photons via integrating up-conversion nanophosphors, which provide us a promising approach to exceed the efficiency limit of single junction organic solar cells.
Keywords: IR light harvesting; Nanophosphors; Organic photovoltaics; Up-conversion

The fabrication of color-tunable organic light-emitting diode displays via solution processing - Guo, Fei; Karl, André; Xue, Qifan; Tam, Kai C.; Forberich, Karen; Brabec, Christoph (Light: Science & Applications, 2017)
Electroluminescent devices based on organic semiconductors have attracted significant attention owing to their promising applications in flat-panel displays. The conventional display pixel consisting of side-by-side arrayed red, green and blue subpixels represents the mature technology but bears an intrinsic deficiency of a low pixel density. Constructing an individual color-tunable pixel that comprises vertically stacked subpixels is considered an advanced technology. Although color-tunable organic light-emitting diodes (OLEDs) have been fabricated using the vacuum deposition of small molecules, the solution processing of conjugated polymers would enable a much simpler and inexpensive manufacturing process. Here we present the all-solution processing of color-tunable OLEDs comprising two vertically stacked polymer emitters. A thin layer of highly conducting and transparent silver nanowires is introduced as the intermediate charge injection contact, which allows the emission spectrum and intensity of the tandem devices to be seamlessly manipulated. To demonstrate a viable application of this technology, a 4-by-4 pixelated matrix color-tunable display was fabricated.
Keywords: color tunable; oLED display; organic light-emitting diode; silver nanowires; solution processing; tandem